Trends in psychiatric emergency visits: insights from France’s largest psychiatric emergency department - Marine Ambar Akkaoui; David Barruel; Valérie Dauriac-Le Masson; Raphael Gourevitch; Alexandra Pham-Scottez (International Journal of Emergency Medicine)
Abstract Introduction Psychiatric emergency departments (EDs) in France have been under pressure from several factors, exacerbated by the COVID-19 pandemic. The pandemic led to an increase in psychiatric disorders, particularly anxiety and depression, with younger people and women being most affected. The aim of this study was to provide a comprehensive description of the trends in the number of visits to the largest psychiatric emergency department in France, with a particular focus on the period preceding and following the advent of COVID-19 pandemic. Methods This retrospective study analyzed data from 69,764 visits to the Centre Psychiatrique d’Orientation et d’Accueil (CPOA) in Paris from 2016 to 2023. Patient data, including demographics, reasons for visit, and diagnoses, were collected and analyzed to identify trends over this period. Results The study observed a 28.5% increase in ED visits from 2016 to 2023. The increase was primarily driven by mood and anxiety disorders, which showed increases of 38.6% and 75.4%, respectively. The average age of patients decreased, reflecting a younger population increasingly affected by psychiatric problems. Interestingly, despite the increase in ED visits, hospital admissions decreased by 11.9%, with a notable decrease in involuntary commitment. Discussion The findings highlight a paradox where increased psychiatric ED visits are not accompanied by an increase in hospital admissions. This suggests a shift toward outpatient care due to systemic factors, including reduced hospital bed availability and challenges in accessing timely outpatient services. This study underscores the need to strengthen outpatient mental health services to effectively manage the growing demand. Further research, especially multicenter studies, is recommended to validate these findings and inform policy changes.